A method for preparing a welded joint based on aluminum-titanium dissimilar metals
Patent Information
- Application Number
- CN202610040592.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-13
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]解决的技术问题:针对现有技术冶金不相容、脆性相增多、裂纹敏感性强及接头性能差等问题,本发明提供一种基于铝钛异种金属的焊接接头的制备方法,采用纯镍过渡层辅助的CMT焊接方法,旨在通过优化过渡层设计、焊接工艺及过程控制,实现高质量、无缺陷的铝/钛焊接接头
1.该制备方法制备得到的焊接接头的平均抗拉强度达到62MPa,且断裂发生在焊缝区域,表现出良好的连接效果。
Smart Images

Figure CN123000185A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of dissimilar metal welding technology, and in particular to a method for preparing a welded joint based on aluminum-titanium dissimilar metals. Background Technology
[0002] Aluminum / titanium dissimilar metal structures combine the low density and high thermal conductivity of aluminum alloys with the high specific strength and corrosion resistance of titanium alloys, making them promising for applications in lightweight manufacturing and other fields requiring lightweight materials. However, aluminum and titanium differ significantly in their physical properties (such as melting point, coefficient of thermal expansion, and thermal conductivity) and chemical properties. In particular, direct welding of the two readily generates brittle intermetallic compounds (IMCs) such as TiAl3, TiAl2, and TiAl in the weld region. These hard and brittle phases severely degrade the joint's plasticity, promoting weld hot cracking, and often accompanied by defects such as incomplete fusion, porosity, and penetration cracks. This results in low joint strength and poor reliability, hindering the design and application of aluminum / titanium composite structures.
[0003] To alleviate the aforementioned problems, existing technologies often employ low-heat-input welding methods (such as laser welding, electron beam welding, and CMT welding) and introduce a transition layer for auxiliary welding. The transition layer material is typically a metallic element (such as Nb, Ni, Cu, etc.) or a combination thereof that can form stable compounds with both aluminum and titanium. By absorbing heat during melting, it reduces the heat input to the low-melting-point base material and alters the metallurgical reaction pathway in the weld zone, preventing the formation of large amounts of harmful Ti-Al intermetallic compounds. Pure nickel is considered a promising transition layer material because it can form various stable ternary and binary compounds with both Al and Ti, and the Al-Ni-Ti phase diagram contains a wide liquid phase range, which is beneficial for suppressing segregation and cracking. However, existing research on the application of pure nickel transition layers combined with CMT processes in aluminum / titanium welding is insufficient, especially regarding process parameter optimization, interfacial reaction control, joint formation mechanisms, and performance regulation, which require further exploration. Summary of the Invention
[0004] Technical problem to be solved: In view of the problems of metallurgical incompatibility, increased brittle phases, strong crack sensitivity and poor joint performance in existing technologies, this invention provides a method for preparing aluminum-titanium dissimilar metal welded joints. It adopts a CMT welding method assisted by a pure nickel transition layer, aiming to achieve high-quality, defect-free aluminum / titanium welded joints by optimizing the transition layer design, welding process and process control.
[0005] Technical solution: A method for preparing a welded joint based on aluminum-titanium dissimilar metals, comprising the following steps: (1) 5052 aluminum alloy and Ti6Al4V titanium alloy with a thickness of 4mm were selected as the welding base materials; (2) Apply a 0.1 mm thick annealed pure nickel strip as a transition layer to the welding end face of 5052 aluminum alloy; (3) The side of the Ti6Al4V titanium alloy base material to be welded is machined to prepare a 45° single-sided bevel; (4) A cold metal transition (CMT) welding equipment was used, with Ti6Al4V welding wire of 1.2 mm diameter as filler material. The wire feeding speed was set to 6.0 m / min, the welding speed to 15 cm / min, the shielding gas to argon, and the gas flow rate to 20 L / min. During the welding process, the welding torch was kept perpendicular to the surface of the workpiece and horizontally offset to the titanium alloy side by 2 mm. (5) After welding is completed, a welded joint based on aluminum-titanium dissimilar metal with uniform structure is obtained.
[0006] The chemical composition of the annealed pure nickel strip in step (2) above meets the following conditions: Ni ≥ 99.9%, Si ≤ 0.02%, Fe ≤ 0.02%, Cu ≤ 0.01%, O ≤ 0.02%, C ≤ 0.02%.
[0007] The protective gas in step (4) above is high-purity argon with a purity of not less than 99.99%.
[0008] In step (4) above, the 5052 aluminum alloy welding end face needs to be mechanically ground to remove the oxide film before welding, and the oil stains need to be cleaned with alcohol; the Ti6Al4V titanium alloy bevel and adjacent area are pickled with a compound 40% HNO3 + 5% HF aqueous solution for 3-5 minutes to remove the surface oxide layer and then dried; wherein the compound aqueous solution contains 40% HNO3 and 5% HF.
[0009] After the welding is completed in step (5) above, an element mixing zone with a width of no more than 300 μm is formed in the original transition layer region of the welded joint. The phases of the element mixing zone include AlNi2Ti, NiTi2, Al3Ni2 and Al3Ni, and the average tensile strength of the joint is not less than 62 MPa.
[0010] The principle of the preparation method of the present invention is as follows: By introducing a pure nickel transition layer, the reaction pathway in the weld zone is altered, leveraging the fact that nickel can undergo metallurgical reactions with both aluminum and titanium but produces phases with lower brittleness. During CMT welding, the transition layer completely melts and diffuses, forming an elemental mixing zone approximately 300 μm wide in situ. Within this zone, the Al-Ni-Ti ternary reaction primarily occurs, generating phases such as AlNi2Ti, NiTi2, Al3Ni2, and Al3Ni, replacing the originally harmful Ti-Al binary brittle compounds (such as TiAl3). Simultaneously, the endothermic melting of the pure nickel layer effectively reduces the heat input to the aluminum alloy side, inhibiting over-melting and reducing the diffusion of aluminum elements to the weld center, thus preventing the formation of penetration cracks. The optimized welding parameters further ensure a stable molten pool and good weld formation, achieving a high-quality joint with no incomplete fusion, no porosity, and complete penetration.
[0011] Beneficial effects: The method for preparing a welded joint based on aluminum-titanium dissimilar metals provided by this invention has the following beneficial effects: 1. The welded joint prepared by this method has an average tensile strength of 62 MPa, and the fracture occurs in the weld area, showing a good connection effect.
[0012] 2. This preparation method has the advantages of stable process, good repeatability, high joint quality and strong applicability, and is particularly suitable for high-end equipment manufacturing field with high requirements for structural performance and lightweighting. Attached Figure Description
[0013] Figure 1 This is a schematic diagram of the preparation process of the welded joint in Example 1.
[0014] Figure 2 The image shows the macroscopic morphology of the welded joint prepared in Comparative Example 1 without the use of a transition layer.
[0015] Figure 3 The macroscopic morphology of the weld front (a) and back (b) of Example 1 is shown.
[0016] Figure 4 This is a diagram showing the element distribution (EDS surface scan) of the weld cross-section in Example 1.
[0017] Figure 5 The image shows the SEM microstructure of the connector center in Example 1.
[0018] Figure 6 The image shows the XRD phase analysis pattern of the weld metal in Example 1.
[0019] Figure 7 The image shows the element distribution curve of the weld interface obtained by SEM line scanning in Example 1.
[0020] Figure 8The image shows a bright-field TEM image of the weld center region and a selected region electron diffraction (SEAD) pattern in Example 1.
[0021] Figure 9 This is a schematic diagram of the formation and phase evolution mechanism of the element mixing zone during the welding process in Example 1.
[0022] Figure 10 The isothermal cross-sectional phase diagrams of the Al-Ni-Ti ternary system of Example 1 at 1127℃ (a) and 900℃ (b).
[0023] Figure 11 The stress-displacement curve of the welded joint in Example 1 is shown.
[0024] Figure 12 The SEM morphology of the tensile fracture surface in Example 1 is shown. Figure 13 This is a Vickers hardness distribution cloud map of the weld cross-section in Example 1. Detailed Implementation
[0025] To make the objectives, content, and advantages of this invention clearer, the invention will be further described below with reference to the accompanying drawings and specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. After reading this invention, any modifications to the invention by those skilled in the art in various equivalent forms fall within the scope defined by the appended claims.
[0026] The materials and instruments used in the following embodiments are from the following sources: The welding wire material was Ti6Al4V titanium alloy welding wire manufactured by ESAB of Sweden, with a wire diameter of Ф=1.2 mm. The substrate was 5052-T6 aluminum alloy and Ti6Al4V titanium alloy sheet with dimensions of 100mm×50mm×4mm. The transition layer was 0.1mm thick pure nickel strip, supplied in annealed condition. The additive manufacturing system built in this experiment was a complete cold metal transition welding system consisting of a Fronex CMT TPS4000 welding machine and a Kawasaki BA006N six-axis welding robot. Example 1
[0027] This embodiment provides a method for preparing a welded joint based on aluminum-titanium dissimilar metals (the preparation process is illustrated in the diagram below). Figure 1 (As shown), the specific steps are as follows: 1. Pretreatment of base material Using 5052 aluminum alloy and Ti6Al4V titanium alloy as base materials, the 5052 aluminum alloy sheet and the Ti6Al4V titanium alloy sheet were cut into specifications of 200mm×100mm×4mm, respectively. Their chemical compositions conform to Table 1 and Table 2 below, respectively. Table 1 shows the chemical composition (wt.%) of 5052 aluminum alloy, and Table 2 shows the chemical composition (wt.%) of Ti6Al4V titanium alloy. A 45° bevel was machined on one side of the Ti6Al4V titanium alloy sheet. The end face of the 5052 aluminum alloy sheet to be welded was mechanically ground and then cleaned with alcohol. The bevel area of the Ti6Al4V titanium alloy sheet was pickled (40% HNO3 + 5% HF, time 4 min) and then dried.
[0028] Table 1 Standard value 0.25 0.40 0.10 0.10 2.2-2.8 0.15-0.35 margin Measured value 0.22 0.44 0.10 0.11 2.63 0.28 margin Table 2 Standard value 0.13 0.01 0.05 5.5-6.75 3.5-4.5 margin Measured value 0.15 0.01 0.05 6.01 3.96 margin 2. Transition layer installation An annealed pure nickel strip of 0.1mm×4mm is tightly applied to the end face of the aluminum plate to be welded and fixed with a clamp to ensure good contact with the substrate.
[0029] 3. Welding parameter settings The robotic CMT welding system was used, with φ1.2mm Ti6Al4V welding wire as filler material, high-purity argon as shielding gas (flow rate of 20 L / min), wire feed speed of 6.0 m / min, welding speed of 15 cm / min, and welding torch perpendicular to the workpiece and offset 2mm towards the titanium side.
[0030] 4. Welding operation Perform cold metal transfer welding to complete the butt joint.
[0031] A schematic diagram of the formation and phase evolution mechanism of the element mixing zone during welding is shown below. Figure 9 As shown, the reaction zone within the welded joint is relatively small, with a relatively concentrated distribution of elements. The proportion of elements varies significantly in different regions, indicating that the metallurgical reaction occurs within the element mixing zone. The width of the nickel element distribution area is significantly greater than the original thickness of the transition layer, suggesting that the transition layer completely melts and diffuses during the welding process. Furthermore, there are boundaries between the aluminum and titanium elements in the distribution area. The transition layer serves to prevent sufficient contact between the aluminum and titanium elements, thus avoiding the formation of brittle and hard intermetallic compounds such as TiAl3.
[0032] 5. Post-weld inspection 1) Macroscopic inspection showed that the weld formation was good on both the front and back sides, with no visible defects. The macroscopic morphology of the weld front and back sides are as follows: Figure 3As shown in a and b, the weld is more uniform after adding a pure nickel transition layer, and the cladding metal has a higher efficiency in filling the weld, achieving complete filling and penetration of the base material. However, due to the addition of the pure nickel transition layer, a small amount of spatter occurs during arc ignition and adheres to the front side of the welded plate, as shown in Figures a and b. Figure 3 As shown in a.
[0033] 2) After the metallographic sample was polished and etched, it was observed under OM and SEM that the transition layer was completely melted, forming an element mixing zone about 300μm wide, without defects such as cracks or pores.
[0034] The results of the element distribution of the weld cross-section (EDS surface scan) are as follows: Figure 4 As shown, Al and Ti are the main elements in the base metal, Ni is the main element in the transition layer, and V is the strengthening element in Ti6Al4V, which exists in the titanium alloy matrix in a dispersed form. Adding V for testing can better determine the melting and flow cladding range of the welding wire and the titanium alloy base metal.
[0035] SEM microstructure of the connector center as follows Figure 5 As shown, the fracture surface exhibits obvious river patterns and cleavage steps, generally consistent with brittle fracture characteristics. However, small-scale dimples are observed in some areas. Upon further magnification, silvery-white precipitates of varying sizes are observed on the fracture surface. It is preliminarily judged that the addition of the transition layer caused nickel to diffuse into the alloy, resulting in the precipitation of some strengthening elements near the grain boundaries. Alternatively, it may be that smaller strengthening phases dispersed in the matrix aggregate and grow due to welding heat input. The larger particles cause higher stress around them, and during tensile testing, these areas cannot pin dislocations like the smaller particles, but instead easily become crack initiation sites. The complete outline of the precipitates indicates that intergranular fracture occurs when the crack propagates to this point during the fracture process.
[0036] 3) XRD and TEM / SAED analyses confirmed that the main phases in the mixing region were AlNi2Ti, NiTi2, Al3Ni2 and Al3Ni.
[0037] XRD phase analysis pattern of weld metal as follows Figure 6 As shown in the figure, the main phases of the weld using a pure nickel transition layer are AlNi2Ti, NiTi2, Al3Ni2, and Al3Ni. Analysis of the diffraction peaks around the high-intensity diffraction peaks indicates that pure nickel is not present in the weld joint. The presence of numerous diffraction peaks may be due to the complex orientation of the intermetallic compounds grown in the welding reaction zone.
[0038] SEM line scan element distribution curve of weld interface as shown in Figure 7As shown, the reaction area within the welded joint is relatively small, and the distribution of each element is relatively concentrated. The proportion of elements varies greatly in different areas, and a nickel accumulation area appears. The width of the nickel distribution area is significantly larger than the original thickness of the transition layer, indicating that the transition layer completely melts and diffuses during the welding process, and there is a boundary between the aluminum and titanium elements in the distribution area. The transition layer plays a role in preventing the aluminum and titanium elements from fully contacting each other, thus avoiding the formation of brittle and hard intermetallic compounds such as TiAl3.
[0039] TEM bright-field image of the weld center region and electron diffraction (SEAD) pattern of the selected region as shown in the figure. Figure 8 As shown in the figure, TEM morphology analysis revealed a large number of precipitates in the weld, along with a relatively high dislocation density. This indicates that stress concentration occurred during the weld cooling process due to the abundance of precipitates. To determine their composition, electron selected area diffraction was used for qualitative analysis of the precipitates in the weld. Figure 8 b~f represent the results of electron selective area diffraction analysis of the precipitated phases in the TEM morphology of the weld center region. After comparative analysis, four sets of diffraction spots were obtained. By calculating the lattice constants a and b and comparing them with the standard PDF card, the phases were found to be AlNi2Ti, NiTi2, Al3Ni2, and Al3Ni, respectively.
[0040] 4) Tensile tests showed that the average tensile strength of the joint was 62 MPa, and fracture analysis showed that it exhibited mixed brittle-ductile fracture characteristics. The isothermal phase diagrams of the Al-Ni-Ti ternary system at 1127℃ (a) and 900℃ (b) are shown below. Figure 10 As shown. Combined with Figure 10 Analysis of the isothermal section of the Al-Ni-Ti ternary phase diagram at 1127℃ shows that when the molten pool temperature drops to this temperature, the main phase product AlNi2Ti precipitates from the liquid phase. When the temperature drops to 900℃, the liquid phase area shrinks, and the AlNi2Ti precipitate remains within the fusion zone without decomposition. Simultaneously, due to the decrease in temperature and the reduction in Ni content within the fusion zone, two groups of elemental metal compounds are locally generated at the edge of the elemental mixing zone.
[0041] The engineering stress-displacement curve of the welded joint is as follows: Figure 11 As shown, the joint fractured in the fusion line region on the aluminum side. The tensile strength of the welded joint was 62 MPa. The addition of the transition layer suppressed the occurrence of welding defects to some extent, but at the same time, the increase in the alloy element content in the fusion zone produced a large number of intermetallic compounds, which led to a decrease in the overall tensile strength.
[0042] SEM morphology of tensile fracture surface as follows Figure 12As shown, the fracture surface exhibits obvious river patterns and cleavage steps, generally consistent with brittle fracture characteristics. However, small-scale dimples were found in some areas. Upon further magnification, silvery-white precipitates of varying sizes and complete outlines were observed on the fracture surface, indicating that intergranular fracture occurred when the crack propagated to this point during the fracture process.
[0043] 5) Vickers hardness test shows that the hardness at the center of the weld is the highest, about 570 HV, and gradually decreases towards both sides of the base material.
[0044] Vickers hardness distribution cloud map of weld cross section as shown in Figure 1 Figure 13 As shown in the figure, the analysis revealed a significant increase in hardness at the in-situ pure nickel transition layer in the weld center, with a maximum hardness of 570.5 HV. This indicates a large stress concentration in this area and that brittle and hard intermetallic compounds are the main reaction zone of the weld. Furthermore, the hardness of the heat-affected zones of the titanium alloy and aluminum alloy base materials also increased to varying degrees. The hardness of the Al-Ni-Ti intermetallic compounds generated in the weld after the addition of the transition layer is significantly lower than that of the Al-Ti intermetallic compounds, effectively preventing the generation of welding hot cracks and stress concentration in the weld. Comparative Example 1
[0045] The difference between Comparative Example 1 and Example 1 is the absence of the transition layer installation in step 2; the macroscopic morphology of the resulting welded joint is as follows. Figure 2 As shown, various welding defects exist at the joint. At the upper end of the joint, where heat input is more concentrated and the arc force is more pronounced, the molten pool has a larger flow range during welding. Due to the significant melting point difference between aluminum and titanium, the titanium and aluminum cannot be infinitely miscible during the mixing of liquid metals in the molten pool. This causes the titanium alloy to solidify before the aluminum alloy, forming dendrites that grow into the unsolidified area, creating an intrusion zone. After adding a pure nickel transition layer, the weld is more uniform, and the cladding metal has a higher efficiency in filling the weld, achieving complete weld filling and penetration of the base material. Post-weld macroscopic analysis did not reveal welding cracks, lack of fusion, or other welding defects. However, because the welding arc in CMT welding has a cycle of extinction and ignition, during the re-ignition process, the welding machine ignites the arc based on the electrical signal collected during welding, which is now higher than the preset welding current and voltage. The addition of a pure nickel transition layer in the weld causes a small amount of spatter to adhere to the front side of the weld plate during arc ignition.
[0046] The comparison between Example 1 and Comparative Example 1 fully demonstrates the feasibility and effectiveness of the method of the present invention. The quality of the obtained aluminum / titanium welded joint is significantly better than that of the traditional welding method without the use of a transition layer.
[0047] The above embodiments have provided a detailed description of the implementation of the present invention. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. The above descriptions are merely preferred embodiments of the present invention and do not limit the scope of the present invention. All equivalent structural changes made based on the content of this specification are included within the scope of the present invention.
Claims
1. A method for preparing a welded joint based on aluminum-titanium dissimilar metals, characterized in that... Includes the following steps: (1) 5052 aluminum alloy and Ti6Al4V titanium alloy with a thickness of 4mm were selected as the welding base materials; (2) Apply a 0.1 mm thick annealed pure nickel strip as a transition layer to the welding end face of 5052 aluminum alloy; (3) The side of the Ti6Al4V titanium alloy base material to be welded is machined to prepare a 45° single-sided bevel; (4) A cold metal transition (CMT) welding equipment was used, with Ti6Al4V welding wire of 1.2 mm diameter as filler material. The wire feeding speed was set to 6.0 m / min, the welding speed to 15 cm / min, the shielding gas to argon, and the gas flow rate to 20 L / min. During the welding process, the welding torch was kept perpendicular to the surface of the workpiece and horizontally offset to the titanium alloy side by 2 mm. (5) After welding is completed, a welded joint based on aluminum-titanium dissimilar metal with uniform structure is obtained.
2. The method for preparing a welded joint based on aluminum-titanium dissimilar metals according to claim 1, characterized in that... The chemical composition of the annealed pure nickel strip in step (2) meets the following conditions: Ni ≥ 99.9%, Si ≤ 0.02%, Fe ≤ 0.02%, Cu ≤ 0.01%, O ≤ 0.02%, C ≤ 0.02%.
3. The method for preparing a welded joint based on aluminum-titanium dissimilar metals according to claim 1, characterized in that: The protective gas in step (4) is high-purity argon with a purity of not less than 99.99%.
4. The method for preparing a welded joint based on aluminum-titanium dissimilar metals according to claim 1, characterized in that: In step (4), the 5052 aluminum alloy welding end face needs to be mechanically ground to remove the oxide film before welding, and the oil stains need to be cleaned with alcohol; the Ti6Al4V titanium alloy bevel and adjacent area are acid-washed with a compound 40% HNO3 + 5% HF aqueous solution for 3-5 minutes to remove the surface oxide layer and then dried; wherein the compound aqueous solution contains 40% HNO3 and 5% HF.
5. The method for preparing a welded joint based on aluminum-titanium dissimilar metals according to claim 1, characterized in that: After the welding is completed in step (5), an element mixing zone with a width of no more than 300 μm is formed in the original transition layer region of the welded joint. The phases of the element mixing zone include AlNi2Ti, NiTi2, Al3Ni2 and Al3Ni, and the average tensile strength of the joint is not less than 62 MPa.
